Efektivitas dan Keamanan Saffron (Crocus sativus) dalam Meningkatkan Kualitas Tidur pada Pasien dengan Gangguan Tidur: Studi Literatur - Ega Fitriana; Nadira Rifda Utami; Risya Lailatilkadri; Masayu Syarinta Adenina (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Sleep disorders are global health problems that impair physiological function, psychological well-being, and overall quality of life. Conventional pharmacological therapies often have limitations and adverse effects, creating a need for safer alternatives. Saffron (Crocus sativus), which contains crocin, crocetin, and safranal, has reported neuromodulatory, anti-inflammatory, and anxiolytic properties that may improve sleep quality. This study aimed to review the scientific evidence regarding the safety and effectiveness of saffron in improving sleep quality among individuals with sleep disorders. The study conducted a systematic literature search in PubMed, ScienceDirect, EuropePMC, and Google Scholar using keywords related to saffron and sleep quality. The inclusion criteria were articles published in English or Indonesian within the last ten years. The exclusion criterion was closed-access articles. Data were analyzed qualitatively based on study design, type of intervention, and primary outcomes. The reviewed studies show that saffron consistently improves sleep quality, as reflected by lower PSQI and ISI scores, increased sleep duration, reduced sleep latency, and improvements in mood, anxiety, and melatonin levels. Its effectiveness appears in healthy individuals and in patients with comorbidities such as diabetes, depression, anxiety, and temporomandibular disorder. Saffron also shows a favorable safety profile without serious adverse effects at doses ranging from 14–30 mg/day to up to 300 mg/day for short-term use. Saffron shows potential as a complementary intervention for improving sleep quality through neuropsychological, anti-inflammatory, and hormonal mechanisms. It is effective and safe as adjunctive therapy for sleep disorders, although long-term studies are still needed. Keywords: saffron, Crocus sativus, crocin, sleep disorder, complementary herbal therapy